Relationship between air pollution (sulfur dioxide) - Kariman, N; Araban, M; Motesadi Zarandi, S; Alavi Majd, H; Ahmadi, M (Advances in Nursing & Midwifery, 2008)
Introduction Low birth weight as a result of premature labor or limited intrauterine growth is the most important measure of neonatal mortality. It has many causes of which air pollution has been recently gained attention. The Purpose of this historical cohort study was to determine the relationship between sulfur dioxide and low birth weight in term neonates of women referring to selected hospitals in Tehran in 2007. Materials and Methods 225 women referring to selected hospitals and residing at 5-Km distance from stations for air pollution measurement were selected. An information form was used to collect data. Its validity and reliability were achieved by content and test-retest methods respectively. Women were divided into 2 groups of exposure (low and high) according to their contact with the pollutant. The groups were matched in terms of factors effective on low birth weight. Results Findings showed a significant relationship between sulfur dioxide and low birth weight (P<0.5, RR=3.96, CI=1.74-8.92). Conclusion With respect to the results, appropriate instructions should be provided for women residing at crowded areas of the city and necessary interventions carried out to decrease this pollutant. Keywords: Low birth weight infant, Sulfur dioxide, Pregnant women.